Methanol as antifreeze agent for cold start of automotive polymer electrolyte membrane fuel cells. (15th March 2019) - Knorr, Florian; Sanchez, Daniel Garcia; Schirmer, Johannes; Gazdzicki, Pawel; Friedrich, K.A.
Graphical abstract: Highlights: Methanol solution is suitable as antifreeze for freeze-thaw cycling of PEMFC MEAs. Antifreeze eliminates performance losses due to freezing for j < 1.6 A cm −2. Antifreeze allows PEMFC operation at sub-zero temperatures during cold-start. Abstract: One challenge for polymer electrolyte membrane fuel cells (PEMFCs) for electric vehicles is to ensure cold start capability and longevity under freeze-thaw (F/T) cycling. Today, PEMFCs undergo dry gas purging to remove residual water before a cold shut-down to avoid degradation due to icing. This study investigates an alternative procedure with alcohol-water solution as antifreeze. In order to demonstrate the suitability of methanol as antifreeze, F/T cycling tests using methanol have been compared with conventional dry gas purging of the cell before F/T cycling. The results show that performance degradation upon F/T cycling is mitigated when flooding the cell with the antifreeze prior to F/T cycling. Specifically, performance losses are observed at high current densities only and the peak performance of the cell does not decrease. Moreover, cold start procedures are examined to allow a start-up of the cell after being soaked with the antifreeze. In this context it is found that PEMFC operation is possible at sub-zero temperature if residual methanol is in the cell. However, residual methanol decreases power density during cold start. Hence, methanol needs to be removed from the cell by reaction or by prolonged water purging to reach nominal power.